ZERO WASTE COLLABORATIVE SHOP DI BANJARBARU - Ajeng Meilifa Kusumaningrum; Mohammad Ibnu Saud (ULM Press, 2021)
Waste is a problem that has become a never-ending topic to get talked about all over the world. Indonesia alone has produced 67 tons of waste only in 2019 by the percentage of organic waste dominating more than half of the total waste. The issuance of a presidential regulation on waste management coupled with a law that regulates sustainable economic policies became the reason why the Zero Waste Collaborative Shop in Banjarbaru gets to design. So the problem that needs to be solved is how to design a Zero Waste Collaborative Shop that can accommodate the interactions between the environment, society, and economy so the three of them could integrate with the surrounding community? Zero Waste is a philosophy that is used as a lifestyle to encourage the cycle of resources so a product can be used sufficiently, and not excessively while the rest of the waste can be reprocessed. The design of the Zero Waste Collaborative Shop will have three problems, which are environmental, social, and economic issues. Therefore, the locality was chosen as the method to assist the Stacking the System concept which is expected to be the solution to these problems. The results of this paper are formulating the concept of planning the commercial space by stacking the permaculture systems, circular economy, and community collaboration, with the outcomes in the form of 1) The implementation of the reuse principle in former office buildings that are not maintained so that it will have new functions 2) Analyzing the climate data surrounding the site so that it is following the needs of the site location 3) Utilizing the permaculture ethical principles, that respect natural resources such as land, water, sun and wind 4) Mapping the utility flow schemes as a model for commercial space 5) Providing space for surrounding communities in the application of Zero Waste to everyday life